A simple mixture of gases is a mixture of ideal gases (Archives of Mechanics - Test, 2006)
If the thermodynamics of fluid mixture has a classical form, then the simple fluid mixture (Müller [1, 2]) has the special form of the state equation (see Eq. (3.5)). Moreover, if such mixture is gaseous, then it is equivalent to the mixture of ideal gases.